2022
DOI: 10.1038/s41598-022-12343-w
|View full text |Cite
|
Sign up to set email alerts
|

Quasinormal modes and shadow of noncommutative black hole

Abstract: In this paper we investigate quasinormal modes (QNM) for a scalar field around a noncommutative Schwarzschild black hole. We verify the effect of noncommutativity on quasinormal frequencies by applying two procedures widely used in the literature. The first is the Wentzel–Kramers–Brillouin (WKB) approximation up to sixth order. In the second case we use the continuous fraction method developed by Leaver. Besides, we also show that due to noncommutativity, the shadow radius is reduced when we increase the nonco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 94 publications
1
11
0
Order By: Relevance
“…To determine the reflection and transmission coefficients, we analyze the scattering process using the semi-classical WKB approach, which has been the subject of recent research in the field [125][126][127]. These coefficients are associated with the effective potential and are represented by complex functions denoted as Λ j (Υ), where Υ is a purely imaginary quantity, and ω corresponds to the real frequency associated with the quasinormal modes.…”
Section: The Wkb Methodsmentioning
confidence: 99%
“…To determine the reflection and transmission coefficients, we analyze the scattering process using the semi-classical WKB approach, which has been the subject of recent research in the field [125][126][127]. These coefficients are associated with the effective potential and are represented by complex functions denoted as Λ j (Υ), where Υ is a purely imaginary quantity, and ω corresponds to the real frequency associated with the quasinormal modes.…”
Section: The Wkb Methodsmentioning
confidence: 99%
“…This remarks are only possible due to existence of exotic matter. Furthermore, it is worth highlighting that the thermodynamic aspects have been extensively studied in various contexts, including cosmological scenarios [40,[136][137][138][139][140][141][142][143][144][145][146][147][148][149] and other related areas [150][151][152][153][154][155]. Finally, in order to provide a general overview of our results, we compare them with the Schwarzschild case in table 3.…”
Section: Schwarzschildmentioning
confidence: 99%
“…In [77,78], employing the Lorentzian distribution, the authors have found logarithmic corrections for entropy as well as the condition for the black hole remnant. In [79], we have investigated the quasinormal modes and the shadow radius of a noncommutative Schwarzschild black hole. We show that, in the zero-mass limit, the shadow ray does not vanish, being proportional to a minimum mass for the finite noncommutative parameter and the black hole becomes a black hole remnant.…”
Section: Introductionmentioning
confidence: 99%